CSF-1 Overexpression Predicts Poor Prognosis in Upper Tract Urothelial Carcinomas. (21st August 2019) - Hsu, Wei-Chi; Lee, Yi-Chen; Liang, Peir-In; Chang, Lin-Li; Huang, A-Mei; Lin, Hui-Hui; Wu, Wen-Jeng; Li, Ching-Chia; Li, Wei-Ming; Jhan, Jhen-Hao; Ke, Hung-Lung
Abstract : Background . Colony-stimulating factor-1 (CSF-1) is a homodimeric glycoprotein. The main role of CSF-1 is as a hematopoietic growth factor that modulates proliferation, differentiation, and survival of macrophages. Moreover, CSF-1 has also been reported to be aberrantly expressed in several human cancers. However, the precise role of CSF-1 in upper tract urothelial carcinomas (UTUC) has not been studied. In this research, we examined the clinical significance of CSF-1 expression in UTUC. Materials and Methods . One hundred twelve cancer tissue samples of UTUC from patients were included in this study, and the other cohort of 35 UTUC were paired cancer-adjacent normal samples. CSF-1 expression was evaluated by immunohistochemistry, and the association of CSF-1 expression with different clinicopathological variables was analyzed. Results . CSF-1 expression was higher in UTUC than in the normal urothelium (P = 0.005 ). The CSF-1 expression was primarily localized in the nucleus and was significantly correlated with tumor size (P = 0.04 ) and patients who had a high stage (P < 0.001 ), distant metastasis (P = 0.006 ), recurrence (P = 0.003 ), and cancer death (P = 0.005 ). High CSF-1 expression was correlated with poor disease-free survival (P = 0.008 ) and cancer-specific survival (P = 0.001 ). Our results also used univariate and multivariable analyses, which found that high CSF-1 expression was an independent predictor of poor disease-free survival (hazard   ratio = 2.56 ;P = 0.007 ) and cancer-specific survival (hazard   ratio = 5.14 ;P = 0.022 ). Conclusions . Our findings indicate that the expression of CSF-1 is a potential prognostic marker for predicting patient survival and recurrence in UTUC.